Kinerja Pelayanan di Dinas Pemberdayaan Perempuan dan Perlindungan Anak Kabupaten Gorontalo dalam Menangani Kasus Kekerasan terhadap Anak - Nandita Filaria Haridji; Sri Yulianty Mozin; Rahmatia Pakaya (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to examine the service performance of the Women’s Empowerment and Child Protection Agency (DPPPA) of Gorontalo Regency in handling cases of violence against children. The study focuses on addressing the service performance from several aspects; (a) productivity, (b) service quality, (c) responsiveness, (d) responsibility, and € accountability. This study was conducted based on the persistently high number of cases of violence against children, which require effective, responsive, and accountable public service handling from the local government. This study employed a qualitative method with a descriptive approach. Data collection techniques included observation, interviews, and documentation, while data analysis used the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings indicate that service productivity is fairly good, as reflected in a clear case-handling flow, though it remains constrained by limited human resources and cross-sector coordination. Service quality is considered positive in terms of empathetic attitudes and the availability of private service spaces; however, the quality of physical facilities and the availability of professional personnel still need improvement. Officers’ responsiveness is relatively quick at the initial stage, but follow-up information on cases is not consistently provided. Responsibility for implementing procedures is in accordance with standard operating procedures, although completion times are often lengthy. Meanwhile, administrative accountability functions well, but the transparency of information to victims still needs to be strengthened.